Answer:
(f - g)(3) = 6
General Formulas and Concepts:
<u>Pre-Algebra</u>
- Order of Operations: BPEMDAS
<u>Algebra I</u>
Step-by-step explanation:
<u>Step 1: Define</u>
f(x) = 4x - 2
g(x) = x + 1
<u>Step 2: Find</u>
<em>Find (f - g)(x)</em>
- Substitute: (f - g)(x) = 4x - 2 - (x + 1)
- Distribute -1: (f - g)(x) = 4x - 2 - x - 1
- Combine like terms: (f - g)(x) = 3x - 3
<em>Find (f - g)(3)</em>
- Substitute: (f - g)(3) = 3(3) - 3
- Multiply: (f - g)(3) = 9 - 3
- Subtract: (f - g)(3) = 6
Answer:
1.6
Step-by-step explanation:
Answer:
AC=15
BC=17
AB=?
According to Pythagore's Theorem: AB² + AC² = BC².
AB² = BC² - AC²
= (17)² - (15)²
= 289 - 225
AB² = 64
AB = √(64)
= 8.
So AB = 8.
A solution to a division problem means it is the quotient. And it tells us the solution to the dividend and divisor.